JENIS-JENIS BURUNG DI DESA PASIR AGUNG KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU PROVINSI RIAU - SULISTIYANINGSIH, EKA (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aimed to determine of birds species in the village Pasir Agung Sub District of Bangun Purba, Rokan Hulu, Riau Province. This study was conducted in September to October 2015, with a survey method. Samples are identified directly in the field. Determination of the research station using purposive random sampling. The research that has been done obtained three orders, 11 families, 14 species with 35 individuals. Bird species are: Columbidae (Sterptopelia chinensis and Geopelia striata), Alcedinidae (Halcyon smyrnensis), Pynonotidae (Pycnonotus cafer, Pycnonotus goiavier and Pycnonotus plumosus), Turdidae (Copsychus saularis), Oriolidae (Oriolus chinensis), Ploceidae (Passer montanus), Sylviidae (Prinia familiaris), Laniidae (Lanius schach), Chloropsidae (Chloropsis sonnerati), Paridae (Parus major) and sturnidae (Acridoptheres javanicus). The predominat species were Geopelia striata (Columbidae), Pycnonotus cafer (Pycnonotidae) and Passer montanus (Ploceidae).